EPIGRAFI INDONESIA: PERAN, KEDUDUKAN, DAN PENGEMBANGANNYA - Tjahjono Prasodjo (BRIN, 1998)
Once again I emphasize that epigraphy is an auxiliary science for archaeology and history. By knowing the position of epigraphy in the constellation of other fields of study, we will know where we stand to then be able to develop this field of epigraphy. The development of the epigraphic study itself turned out to be quite bright. There is still much we can do to increase the quantity and quality of epigraphy research.